Remediation of organic compounds in wastewater by integrated anaerobiosis and phyco-remediation process - Vergara, Donicer E. Montes; Corderos, Alexander Pérez; Mendoza, Yelitza Aguas (Journal of Ecohumanism, 2024)
The cleaning or purification of wastewater is becoming increasingly important due to the increase in population and the growth of industries in all countries of the world, at the same time the requirements of wastewater treatment regulations are becoming more stringent, so it is necessary to create new purification techniques that are not only more efficient but also more sustainable and cleaner. The objective of the present study was to evaluate in the field the efficiency in the process of pollutant removal in wastewater in streams using the combination of anaerobiosis technique and microalgal consortium. For the process, an experiment was designed in a tank with the presence of anaerobic bacteria and the efficiency of the bacteria in the removal of pollutants was evaluated for 24 hours. After this time, the water was deposited in pools with the presence of microalgae consortium, leaving the process for 20 days. The presence of physical and chemical contaminants was evaluated before the experiment during anaerobiosis and microalgal consortium. The results of the in vivo test indicate that the removal process when subjected to microalgae consortium was more efficient showing a percentage of removal result higher than 62% for physical and chemical parameters. The microalgae consortia used in this study have the capacity to grow well in wastewater and show efficiency in the removal of pollutants after 10 days with high efficiency in the removal of pollutants and with the possible reuse of the water obtained from the process for other agricultural activities.